Free radical-mediated photocyclization of triphenylphosphindole oxides for photoactivated and self-reported lipid peroxidation - Li, Jianqing (2024)
Photocyclization is demonstrated as a powerful tool for building complicated polycyclic molecules. And efficient photocyclization is competent as an artful strategy to develop photo-responsive smart materials. Herein, an efficient free radical-mediated photocyclization for triphenylphosphindole oxide (TPPIO) derivatives to generate tribenzophosphindole oxide (TBPIO) derivatives at ambient condition is reported. The reaction mechanism and substituent effect on photocyclization efficiency are thoroughly investigated. Additionally, photophysical and photochemical properties of TPPIO and TBPIO derivatives are measured for comparison and deeply deciphered by theoretical calculation. TPPIO derivatives own typical aggregation-induced emission feature but barely generate reactive oxygen species (ROS), while TBPIO derivatives experience aggregation-caused quenching but show efficient Type I ROS generation capacity. Further, in vitro experiments demonstrate that this photo-conversion can efficiently occur in situ in living cells to activate photodynamic therapy (PDT) effect to trigger lipid peroxidation with selective fluorescence "light up" in lipid droplet area under continuous irradiation. This work extends the optoelectronically and biologically interesting phosphindole oxide-containing π-conjugated systems through an efficient synthetic strategy, provides in-depth mechanistic descriptions in the aspects of reaction and property, and further presents their great potentials for photoactivated and self-reported PDT.